Personal Guidance for Students with Special Needs through Self-Care Programs - Lukman Lukman Harahap; Galih Fajar Fadillah; Anni Nurul Hidayati (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
This study examined the implementation of a self-care development program integrated within a personal guidance framework for students with special needs, focusing specifically on dressing skills. This research uses a qualitative descriptive design. Participants were purposively selected, including one special education assistant teacher, two students with intellectual disabilities, three classroom teachers, and three parents. Data were collected through semi-structured interviews, observations, and documentation. Data were analyzed using thematic analysis with data triangulation. Findings indicate that the self-care program, which includes role-playing, demonstrations, and assignments, effectively encourages student independence, particularly in dressing. The success of this program depends on collaboration between families and schools, including special education teachers and classroom teachers who act as counselors. Although limited parental time and social stigma pose challenges for inclusive schools, the self-care program has the potential to instill sustainable behavioral reinforcement. Through this research, educational practitioners and policymakers can consider developing a self-care program, and school counselors in special schools can collaborate with special education teachers and classroom teachers to facilitate educational services for children with special needs.